Sharks in the arts - Westbrook, Vivienne, author.
1 online resource (216 pages)
Keywords: "This book is the most thorough exploration to-date of the many ways in which a wild creature has been absorbed, reimagined and represented across the ages in all of the major art forms. The authors consider not only how the identity of sharks in the natural environment became incorporated into a cultural environment but also how sharks came to be considered the most feared creatures in the open oceans as a consequence of this incorporation. Yet sharks are especially important in helping to maintain a balance that is essential to the health of the oceans. The book begins with a treatment of the three sharks at the top of global shark attack file from scientific, economic and environmental perspectives. Subsequent chapters engage with cultural representations of sharks in poetry, drama, art, novels, screenplay adaptations and films. Through an exploration of the ways in which sharks have been represented in human culture through the centuries this book alerts the global community to the importance of sharks as a common cultural heritage. It aims to change perceptions of sharks so that they can become more revered than feared. The authors of this book argue that an increased understanding of sharks should lead to the development of better strategies for shark and human interactions.This book will be of great interest to researchers and students of the Environmental Humanities, Cultural History and the Arts. It is also excellent supplementary reading for courses in Zoology and Marine Science."--Provided by publisher.